Efficacies of rapid agglutination tests for identification of methicillin-resistant staphylococcal strains as Staphylococcus aureus. - Piper, J (1988)
Four commercially available rapid agglutination tests for the identification of Staphylococcus aureus were compared with the tube coagulase test for the identification of 300 methicillin-resistant isolates of staphylococci. Isolates tested included 207 methicillin-resistant S. aureus and 93 coagulase-negative staphylococci, collected from five medical centers. Strain variability was documented by phage typing and antimicrobial susceptibility patterns. Results of rapid identification tests ranged between 82 and 86% sensitivity, significantly poorer than the 98% sensitivity which the tube coagulase test provided.